DETERMINAN KINERJA KEUANGAN: SYSTEMATIC LITERATURE REVIEW - Edy Zulfiar (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This article aims to synthesize prior studies on the determinants of financial performance in companies and public organizations through a Systematic Literature Review. The data were taken from an extraction file containing 40 articles and were screened using inclusion criteria related to publication year, topic relevance, research focus, and metadata completeness. A total of 32 articles published between 2016 and 2024 were analyzed using thematic analysis. The findings show that financial performance studies are dominated by liquidity, leverage, profitability, working capital, firm value, capital structure, good corporate governance, corporate social responsibility, intellectual capital, sustainability reporting, and financial distress. Profitability indicators such as ROA, ROE, and EPS tend to show the most consistent relationship with firm value, stock return, and profit. Liquidity and leverage show mixed results because their effects depend on sector, measurement, and model design. The review also finds that governance and sustainability variables are increasingly important, yet prior studies remain fragmented by sector and observation period. Future research should build integrative models that combine financial ratios, governance, sustainability, and external conditions to produce stronger explanations of financial performance.